PERAN MEDIA SOSIAL SEBAGAI SUMBER BELAJAR PAI: Analisis Inovasi dan Distorsi Nilai - Moh Said Aqil Hasan; Faisol Hakim (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
In the digital era, social media has become an important medium in conveying Islamic teachings and learning Islamic Religious Education (PAI). This research is a descriptive qualitative study with a document study and case study approach. This study analyzes the video content of "Belajar Islam Pake Logika" by Ustaz Felix Siauw in the channel Raymond Chin on YouTube platform, focusing on the rational approach in digital preaching as an innovation in PAI learning. Ustaz Felix emphasized the importance of using reason and logic in understanding Islamic teachings, and criticized the low level of religious literacy in Indonesia, which only reached 0.06%. This approach is considered effective in bridging Islamic teachings with the more critical and visual way of thinking of the digital generation. Although social media offers great potential in making religious learning more interesting and contextual, challenges still arise, such as disinformation, simplification of teachings, and the emergence of pseudo-authority based on popularity. Therefore, strong digital and religious literacy is needed so that people are able to sort information critically. The novelty of this study lies in the emphasis on the logical approach in digital preaching and its relevance as a moderate and inclusive learning method. This study recommends collaboration between educators, religious figures, and digital experts to build an adaptive, knowledge-based, and Islamic-value-based da'wah ecosystem. The limitation of this study is the single focus on one figure and one content, without empirical data from the audience. However, this study provides an initial contribution in understanding the transformation of Islamic da'wah through social media in the digital era.